2022
DOI: 10.1038/s41598-022-11174-z
|View full text |Cite
|
Sign up to set email alerts
|

Eye movement analysis of children’s attention for midline diastema

Abstract: No previous studies have investigated eye-movement patterns to show children’s information processing while viewing clinical images. Therefore, this study aimed to explore children and their educators’ perception of a midline diastema by applying eye-movement analysis using the hidden Markov models (EMHMM). A total of 155 children between 2.5 and 5.5 years of age and their educators (n = 34) viewed pictures with and without a midline diastema while Tobii Pro Nano eye-tracker followed their eye movements. Fixat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…15 Hence, future studies could employ eye movement analysis with hidden Markov models to overcome the limitations identified in the present study's view pattern and diagnostic competence aspects. 16,17,18 Using a think-aloud protocol, including a range of clinical images with no time constraints in viewing, and involving the entire cohort of students with no information bias strengthens the study findings. To our knowledge, the present study is the first to explore students' gaze behavior and diagnostic competence while viewing clinical images, thus, precluding possible direct comparisons.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…15 Hence, future studies could employ eye movement analysis with hidden Markov models to overcome the limitations identified in the present study's view pattern and diagnostic competence aspects. 16,17,18 Using a think-aloud protocol, including a range of clinical images with no time constraints in viewing, and involving the entire cohort of students with no information bias strengthens the study findings. To our knowledge, the present study is the first to explore students' gaze behavior and diagnostic competence while viewing clinical images, thus, precluding possible direct comparisons.…”
Section: Discussionsupporting
confidence: 55%
“…Hence, if the fixation is on the left of an image, the participants cannot saccade further left, thus initiating an oscillating movement from left to right 15 . Hence, future studies could employ eye movement analysis with hidden Markov models to overcome the limitations identified in the present study's view pattern and diagnostic competence aspects 16,17,18 …”
Section: Discussionmentioning
confidence: 93%
“…In addition, the children and their educators differed in their preferred looking behavior while looking at a midline diastema. 45 Celine et al 46 observed that children have inherent preferences for where they fixate when viewing images of a dental operatory. Furthermore, their research supported observations that children fixated most on the dentist's face, particularly the circumoral area when they looked at the dentist.…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Cho et al 44 reported that children with the distributed pattern shifted their fixations between images showing traumatic dental injuries. In addition, the children and their educators differed in their preferred looking behavior while looking at a midline diastema 45 . Celine et al 46 observed that children have inherent preferences for where they fixate when viewing images of a dental operatory.…”
Section: Discussionmentioning
confidence: 99%
“…H. F. Chan et al, 2022; F. H. F. Chan, Suen, et al, 2020; Cho et al, 2022a, 2022b, 2022c), gaze perception (S. K. W. Chan et al, 2022), sustained attention to response (Lee et al, 2021), website viewing (Eckhardt et al, 2013), video viewing (Zheng, Ye, & Hsiao, 2022), scene perception (Hsiao, Lan, et al, 2021), reading (Liao et al, 2022), and visual search (Hsiao, Chan, et al, 2021).…”
Section: Methodsmentioning
confidence: 99%